EFEKTIVITAS PENYALURAN DANA USAHA EKONOMI DESA – SIMPAN PINJAM (UED-SP) KEPADA MASYARAKAT DI DESA SUNGAI SALAK, KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Lusiana "; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Poverty is not only about economic issues, but the end result interrelation of social factors, economic, political and cultural. The number of poor people caused the economic growth to be slow. One form of government concern towards this is to create a program that Village Empowerment Program (PPD). In PPD, there are several forms of empowerment, one of which is a program of Rural Economic Enterprises - Savings and Loans (ued-SP) is in the form of government to provide loans or venture capital funding to communities to develop businesses in the community to do so as to improve the village economy. This study aims to determine the effectiveness of the distribution of Fund Business Economy Village - Savings and Loans (ued-SP) and the factors that influence the effectiveness of channeling funds ued-SP in Sungai Salak Rambah Samo District of Rokan Hulu.The theory used is the theory of steers. This study uses descriptive qualitative data collection techniques of observation and interviews. The technique used in determining the informants of this study was purposive sampling technique.From the analysis of qualitative descriptive data found that the effectiveness of the distribution of Fund-SP ued in Sungai Salak District of Rokan Hulu Rambah Samo has been quite effective. It is seen from the participation of the community to use the proceeds from the SP-ued as venture capital, the smooth return of capital to the ued-SP and meningkatnay economy. In this research note that the factors that influence the effectiveness of channeling funds ued-SP in Sungai Salak District of Rokan Hulu Rambah Samo among other factors or not the organization is able to adapt to the environment and of the results of the research institute SP-ued in Sungai Salak already quite capable to adapt to the environment, both the community and the environment of the organization. Target Funds that are less effective, work productivity. Keywords: Effectiveness, Funds Distribution ued-SP